2020
DOI: 10.1016/j.eclinm.2020.100354
|View full text |Cite
|
Sign up to set email alerts
|

What are the underlying transmission patterns of COVID-19 outbreak? An age-specific social contact characterization

Abstract: Background COVID-19 has spread to 6 continents. Now is opportune to gain a deeper understanding of what may have happened. The findings can help inform mitigation strategies in the disease-affected countries.Methods In this work, we examine an essential factor that characterizes the disease transmission patterns: the interactions among people. We develop a computational model to reveal the interactions in terms of the social contact patterns among the population of different age-groups. We divide a city's

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
113
0
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 144 publications
(128 citation statements)
references
References 16 publications
(24 reference statements)
4
113
0
11
Order By: Relevance
“…Finally, our subgroup analysis on different age groups revealed that, in the study period, the overall distribution of all-cause admissions did not change from previous years. However, focusing on distribution of infectious disease admissions, we observed a 227.6% increase in adults (N2019 = 199 vs. N2020 = 652), a 174.5% increase in elderly (N2019 = 153 vs. N2020 = 420), and a 111.1% increase in oldest old (N2019 = 54 vs. N2020 = 114); thus, suggesting a more severe impact of COVID-19 on the admission of patients belonging to the adult group, as observed by other authors [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…Finally, our subgroup analysis on different age groups revealed that, in the study period, the overall distribution of all-cause admissions did not change from previous years. However, focusing on distribution of infectious disease admissions, we observed a 227.6% increase in adults (N2019 = 199 vs. N2020 = 652), a 174.5% increase in elderly (N2019 = 153 vs. N2020 = 420), and a 111.1% increase in oldest old (N2019 = 54 vs. N2020 = 114); thus, suggesting a more severe impact of COVID-19 on the admission of patients belonging to the adult group, as observed by other authors [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 71%
“…Epidemiological studies on SARS-CoV-2 have emphasized the importance of heterogeneity in transmission and the need for measuring transmission events and variations at the individual levels [7][8][9][10]. These studies have emphasized the importance of heterogeneity information in addition to estimating basic reproduction number.…”
Section: Discussionmentioning
confidence: 99%
“…Mathematical modelling methods are mostly adopted for assessing population-level heterogeneity of SARS-CoV-2 infections. Modelling studies have estimated the heterogeneity in terms of over-dispersion levels and proportional variations in transmission based on simulations and assumptions [7][8][9][10]. In this background, attempts to measure individual patient-level heterogeneity in SARS-CoV-2 context using real world data could be of direct public health relevance.…”
Section: Introductionmentioning
confidence: 99%
“…To achieve this goal, the first priority is to assess the epidemiological characteristics of the COVID-19 pandemic in each country. Because populations in different countries have different contact patterns, the epidemiological parameters (e.g., the basic reproduction number R 0 ) of COVID-19 may also vary in different countries [24,25]. Even in the same country, the epidemiological parameters measured with different data at different stages may also be different.…”
Section: Discussionmentioning
confidence: 99%